Bahasa Arab sebagai Bahasa Lintas Zaman (Systematic Literature Review): Bahasa Arab sebagai Bahasa Lintas Zaman (Systematic Literature Review) - Ahmad Rizki Nugrahawan; Zuriyati Zuriyati; Ifan Iskandar (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
This article aims to examine the role of Arabic as a language across eras through a literature review approach. Arabic has a long history as a literary, scientific and religious language that has had a major impact on various fields of knowledge and daily life. Using the literature review method, this article investigates the development of the Arabic language over time, focusing on its contribution to scientific research, classical literature, and cultural heritage. In scientific literature, Arabic played a significant role in the development of science, mathematics, and medicine during the Islamic Golden Age. Meanwhile, in classical literature, Arabic poetry and prose have become the basis for world literature. This article also highlights the influence of Arabic in religious contexts, especially as the language of the Koran, which has had a profound impact on the spiritual and ethical life of Muslim communities. In addition, this article illustrates how Arabic remains relevant in the modern era, especially in the context of literary language, Islamic education, and international communication. This literature review provides a comprehensive picture of how Arabic continues to maintain its superiority as a language across eras, through changing times while remaining the center of thought, knowledge and identity for the people who own it.